Spiritual care in palliative contexts: perspectives from Hindu family caregivers – a scoping review - Mohamad Ismail, Mohamad Firdaus; Mohd Romzi, Nurul Syakila Izzati; Shahadan, Siti Zuhaidah (Penerbit UnIPSAS, 2024)
This scoping review examines spiritual care in palliative settings from the perspective of Hindu family caregivers, utilizing articles from ProQuest, ScienceDirect, and PubMed, and applying the Joanna Briggs Institute Critical Appraisal Tool. By analyzing eleven studies published between 2019 and 2023, we uncover how Hindu spirituality influences care at the end of life, highlighting themes such as the Concept of Death, Spiritual Needs, and Caregiving Challenges. Findings reveal the critical role of family in providing spiritual support, the blend of religious rituals with caregiving, and the array of challenges faced by caregivers, including emotional and financial burdens. The review advocates for palliative care models that integrate Hindu spiritual practices, addressing the need for culturally sensitive care that respects the spiritual beliefs of Hindu patients and their caregivers. Ultimately, this review underscores the necessity of a holistic approach to palliative care that accommodates spiritual needs within Hindu families. It advocates for the inclusion of transcultural care principles, especially significant for Muslim nurses who are prominently represented in the profession. By integrating these insights, healthcare providers can offer culturally sensitive and spiritually respectful care to patients of diverse backgrounds. This approach not only bridges cultural divides but also enriches the palliative care experience for all involved..